1997
DOI: 10.1038/bjc.1997.528
|View full text |Cite
|
Sign up to set email alerts
|

B7-1 (CD80) as target for immunotoxin therapy for Hodgkin's disease

Abstract: Summary In this preclinical study, the potential applicability of an anti-B7-1 immunotoxin (IT) line Raji (IC50 10-11 M), R-S cell lines HDLM2, KM/H2 and L428 and also against a B7-1 -transfected epithelial cell line, A431, whose parental line lacks expression of B7-1. In clonogenic assays with Raji cells or KM/H2 cells, a 3-or 4-log kill, respectively, was observed. No cytotoxicity was found against the B7-1-epithelial and endothelial cell lines or against haematopoietic progenitor cells. In conclusion, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
(19 reference statements)
1
19
0
Order By: Relevance
“…Inhibitors of the JAK/STAT pathway have been investigated mostly in vitrodspecifically, AZD1480 [97] and lestaurtinib [98]. Targeted therapy against surface receptors of the HRS cells includes anti-RANK ligand antibody and anti-CD80 antibody (galiximab) [99]. Noncellular targets of the microenvironment include extra domain B of fibronectin (ED-B-FN), because it is expressed stronger on newly formed vessels in lymphoma-involved lymph nodes (I 131 -ED-B-FN) [100].…”
Section: Prospective Therapeutic Solutions and Possibilities Of Targementioning
confidence: 99%
“…Inhibitors of the JAK/STAT pathway have been investigated mostly in vitrodspecifically, AZD1480 [97] and lestaurtinib [98]. Targeted therapy against surface receptors of the HRS cells includes anti-RANK ligand antibody and anti-CD80 antibody (galiximab) [99]. Noncellular targets of the microenvironment include extra domain B of fibronectin (ED-B-FN), because it is expressed stronger on newly formed vessels in lymphoma-involved lymph nodes (I 131 -ED-B-FN) [100].…”
Section: Prospective Therapeutic Solutions and Possibilities Of Targementioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24] Cell culture conditions and the provenance, references, cellular origin and characterization of the remaining cell lines used in this study are given in Ref. 25.…”
Section: Cells and Culturementioning
confidence: 99%
“…Preclinical data demonstrated that an anti-B7-1 immunotoxin had significant anti-tumor activity in HL-cell lines and minimal toxicity to CD34+ hematopoietic stem cell. 14,15 Galiximab is a primatized IgG1 monoclonal antibody, which binds to CD80 with high affinity and induces cell death via antibody-dependent cell-mediated cytotoxicity (ADCC). Smith et al studied the clinical activity of single agent Galiximab in patients with rel/ref HL not eligible for or had failed HDC-ASCT/AlloSCT.…”
Section: Cd80 (B7-1)mentioning
confidence: 99%